JUDICIAL PARDON: ANTARA ABUSE OF PARDON POWER DAN PEMBAHARUAN HUKUM PIDANA - Jayusman, Dandi; Gusnawati, Dita; Fathi, Muhammad (Justitia et Pax, 2024)
After 78 years of being subject to the Dutch legal legacy of Wetboek van Strafrecht (WvS), on December 6, 2022, Indonesia officially separated itself from Law Number 1 of 1946. Article 51 of Law Number 1 of 2023 contains the new concept of judicial pardon, a new addition to Indonesian criminal law. This study aims to analyse the formulation of the concept of judicial pardon in Law Number 1 of 2023 on the Criminal Code (KUHP) and examine indications of abuse of power by judges in the formulation of judicial pardon. This study employs a juridical-normative research method, which involves a legal review of the Law Number 1 of 2023, a conceptual approach to analyse the objectives and direction of policy, and a comparative approach to examine the formulation of judicial pardon in various countries. The study utilizes secondary data or library research. Based on the conducted discussion, it is evident that the concept of judicial pardon has been in existence for a considerable amount of time and has been implemented in various countries. We should guide Indonesia's adoption of the judicial pardon concept by studying its formulation in various other countries. Law Number 1 of 2023 formulation of the concept of judicial pardon is still considered incomplete, ambiguous, multi-interpretable, and susceptible to legal abuse. As a result, the concept of judicial pardon can potentially be misused by judges who have personal interests, resulting in abuse of pardon power, particularly in corruption cases.